PENGARUH KOMPENSASI FINANSIAL DAN DUKUNGAN MANAJEMEN PADA KINERJA AUDITOR INTERNAL DENGAN PERIODE PENUGASAN SEBAGAI VARIABEL PEMODERASI - Paramarta, Aditya; Ardiana, Agus (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aims to determine how the effects of the financial compensation and support management on the performance of the internal auditor as well as the moderating effects of internal auditor assignment period to the effects of financial compensation and performance management support of internal auditors in Automotive Company in Denpasar. This study uses 40 respondents internal auditor who works in automotive company in Denpasar, Bali to operate variable compensation financial and management support as independent variables, the period of assignment as a moderating variable, and the performance of the internal auditor as terikat.Teknik variable data analysis used in this study Moderate Regression is Alalysis (MRA). The results showed that the financial compensation does not affect the performance of the internal auditors, management support positive effect on the performance of the internal auditors, and the assignment period will not strengthen the influence of financial compensation and support management on the performance of the internal auditor.
Keywords: financial compensation, management support, the assignment period, the performance of the internal auditor